Polycystic ovarian syndrome among young women of a university in central Gujarat - A cross-sectional study - Kalpita Shringarpure; Rajendra Baxi; Margi Sheth; Purvi Patel; Vidhi Parmar; Sushma Baxi (Wolters Kluwer Medknow Publications, 2023)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common reproductive endocrinological disorders affecting 6%-8% of women in reproductive years. An early liberal PCOS screening appears to be a cost-effective strategy, benefiting earlier diagnosis and intervention. Objectives: The objectives are to measure the prevalence of PCOS and factors associated with PCOS among young girl students of a University in Central Gujarat. Materials and Methods: All consenting girl medical students enrolled in MBBS curriculum during 2013-2017 were given a self-administered questionnaire (for signs and symptoms of PCOS), taking due prior permissions; during January 2018-June 2019. Using Rotterdam (2006) criteria, those who were screened for PCOS were subjected to abdominal ultrasonography (USG) and if required, laboratory investigations (random blood sugar, thyroid-stimulating hormone, and free testosterone). The proportion of young women having PCOS as per the Rotterdam and European Society for Human Reproduction and Embryology (EHSRE) Criteria are reported. Results: The study enrolled 308 girl medical students. More than one-tenth of the study participants (11.7%, 36/308) had confirmed PCOS (Rotterdam Criteria). As per the EHSRE criteria, 24/36 had classic PCOS, 11/36 had ovulatory phenotype, and 01/36 had the non-hyperandrogenic phenotype PCOS. USG was required in 123/308 (39%); of which 91 consented and 16/91 (18%) had conclusive PCOS. Twenty-three girls required laboratory investigations, of which two had abnormal values suggestive of PCOS. Irregular menses and hirsutism were significantly associated with the PCOS (P < 0.05). Conclusion: The proportion of young medical students with PCOS was 12%. Irregular menses and hirsutism were significantly associated with PCOS.